Elderly‐ versus younger‐onset rheumatoid arthritis: Higher levels of ultrasound‐detected inflammation despite comparable clinical disease activity. Issue 2 (30th January 2013) - Dejaco, Christian; Duftner, Christina; Wipfler‐Freissmuth, Edith; Weiss, Helmut; Schneider, Thomas; Schirmer, Michael
Abstract Objective To compare ultrasound‐verified joint inflammation between elderly‐onset rheumatoid arthritis (EORA) and younger‐onset rheumatoid arthritis (YORA) patients. Methods We conducted a retrospective analysis of 145 consecutive rheumatoid arthritis patients routinely assessed by sonography of wrists, metacarpophalangeal joints, and proximal interphalangeal joints, including semiquantitative scoring of synovial hypertrophy/effusion (SH/E) and power Doppler (PD) signals. Global ultrasound (GU) scores were calculated adding SH/E and PD results. EORA was defined by disease onset at age ≥60 years. Number of tender joints and swollen joints, global assessment of disease activity by physician or patient, Disease Activity Score in 28 joints (DAS28), Clinical Disease Activity Index (CDAI), and Simplified Disease Activity Index (SDAI) scores were recorded. Respective values for disease activity were accounted for in group comparisons using SPSS statistical software (version 18.0). Results Seventy patients were diagnosed with EORA (mean ± SD age 71.0 ± 7.3 years, 81.4% women) and 75 patients with YORA (mean ± SD age 46.8 ± 10.2 years, 86.7% women). EORA patients had higher GU scores (median 18.5 [interquartile range (IQR) 17.0] versus 12.0 [IQR 15.0], P = 0.009) and SH/E scores (median 12.0 [IQR 10.0] versus median 9.0 [IQR 9.0], P = 0.004) than patients with YORA. Patients with EORA were more likely to show PD signals in at least 1 joint than YORA patients (85% versus 72%; odds ratio 3.9 [95% confidence interval 1.3–11.5], P = 0.015). DAS28, CDAI, and SDAI scores did not differ between the groups. The sonographic pattern of joint involvement was similar in both groups, with active inflammation most commonly presenting at the wrists. Conclusion Ultrasound examination indicated higher inflammatory burden in EORA patients than in YORA patients despite similar clinical disease activity.